Okoljska arheologija in paleoekologija Palinologija, arheobotanika in arheozoologija - Andrič, Maja (ZRC SAZU, Založba ZRC, 2016)
[Environmental Archaeology and Palaeoecology:Palynology, Archaeobotany and Archaeozoology]Plant and animal remains, which are found on archaeological sites and in lake/marsh sediments, are a good source of information about past economy, environment, food procurement, and the adaptation of people to changeable environmental conditions in various archaeological time periods. However, all these data need to be collected and interpreted. With the first manual presenting palynology, archaeobotany and archaeozoology fields of research in Slovenian language, this task should be more easily achievable.